PROFILE OF MEN SUFFERING FROM SEXUALLY TRANSMITTED INFECTIONS IN PAKISTAN - Rehan, N. (Journal of Ayub Medical College Abbottabad, 2003)
Background: To evolve effective prevention and efficient treatment strategies for sexually transmitted infections (STIs) in a country, comprehensive understanding of the prevalent STI and their modes of transmission is needed. The aim of this present study was to generate such data for Pakistan. Method: The study was conducted between June 1999 and September 1999 in four provincial capitals. In each city, data were collected from one or more teaching hospitals and a number of general practitioners. During this period, 465 men suffering from STIs were interviewed. Results: The mean age of study population was 31.9±8.6 years, 60% were married, 58.3% urbanites, 81.7% living with their families and 83.3% smokers. Only 10.5% were drug addicts. Out of 465 cases, 27.5% cases had gonorrhoea, 31.6% syphilis, 17.2% chancroid, 18.3% herpes, 5.2% chlamydial infections while only one case (0.2%) was HIV positive. Most men (55%) acquired the infection heterosexually, 11.6% through homosexuality, 18.4% through bisexual relations and 2 men (0.5%) reported bestiality. Among 78.1% of those contracting the infection heterosexually, the source of infection was a sex worker. None acquired infection through his wife. The knowledge about STIs was very poor. Wrong notions were prevalent. Conclusions. The pattern of STIs is different from developed countries. Those acquiring STIs in Pakistan were older, married and living with their families whereas in developed countries most men acquiring STIs are younger, unmarried and living alone. Key Words: Sexually Transmitted Infections, Gonorrhoea, Syphilis, Chlamydial Infections, Pakistan.